Tuturan Pujian Pada Penutur Bilingual Indonesia-Madura Di Probolinggo: Pendekatan Psikolinguistik - Nadira Rahmasari; Sofwan Hadi; Ekka Zahra Puspita Dewi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to determine the forms and types of praise utterances within the Indonesian–Madurese bilingual community in Probolinggo. Viewing praise as a communication form reflecting psychological and cultural values, this research employs a psycholinguistic approach. Data were collected through non-participant observation by observing and recording daily conversations in Leces, Probolinggo Regency. The data were then transcribed, classified, and analyzed descriptively. The results indicate that praise utterances manifest in various forms across all age groups, from infants to the elderly. These compliments target aspects of appearance, ability, activity, traits, and creative work. Furthermore, praise utterances serve essential social functions to strengthen relationships, express affection, foster harmony, and maintain politeness in community interaction. This study significantly contributes to enriching psycholinguistic literature, particularly regarding the sociolinguistic dynamics and use of praise utterances within the Indonesian-Madurese bilingual community in Probolinggo.